2010
DOI: 10.1177/0748233710386408
|View full text |Cite
|
Sign up to set email alerts
|

Roles of reactive oxygen species and mitochondria in cadmium-induced injury of liver cells

Abstract: The roles of reactive oxygen species (ROS) and mitochondrial damage in the cadmium (Cd)-induced injury of liver cells were studied by using N-acetyl-L-cysteine (NAC) and acetyl-L-carnitine hydrochloride (ALCAR). After exposure of experimental rats to cadmium (Cd) for 16 h, mitochondrial membrane potential (MMP), ROS production, glutathione peroxidase (GSH-Px) activity, glutathione (GSH) content, malondialdehyde (MDA) content and DNA single-strand break (DNA-SSB) were analyzed. Loss of MMP, increase of ROS prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Since a similar effect was observed with CdCl 2 , the disruption of mitochondrial membrane potential could also result from the effects of cadmium, which has also been previously reported by other groups ( Bolduc et al. , 2004 ; Liu et al. , 2011 ; Mao et al.…”
Section: Discussionsupporting
confidence: 83%
“…Since a similar effect was observed with CdCl 2 , the disruption of mitochondrial membrane potential could also result from the effects of cadmium, which has also been previously reported by other groups ( Bolduc et al. , 2004 ; Liu et al. , 2011 ; Mao et al.…”
Section: Discussionsupporting
confidence: 83%
“…Numerous studies have already shown the protective role of hormones like melatonin [ 43 , 44 , 45 ], antioxidative vitamins [ 27 , 40 , 46 , 47 , 48 , 49 ], and antioxidants such as N -acetylcysteine (NAC) [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals had the potential to induce toxicological effects and led to the accumulation of ROS [ 31 ]. As lethal heavy metals in the environment, Cd could also stimulate the formation of ROS, thereby causing oxidative damage to tissues and resulting in the loss of the cell functions [ 8 , 9 , 32 ]. Therefore, we speculated that Cd could damage the body primarily through oxidative stress.…”
Section: Discussionmentioning
confidence: 99%